2020
DOI: 10.1177/0300060520958960
|View full text |Cite
|
Sign up to set email alerts
|

Highly oxidized low-density lipoprotein does not facilitate platelet aggregation

Abstract: Objective This study aimed to examine whether oxidized low-density lipoprotein (oxLDL) facilitates platelet aggregation, which is one cause for development of cardiovascular disease. Methods The susceptibility of platelets to aggregation was monitored by light transmittance aggregometry and a laser light scattering method using low-density lipoprotein (LDL) and oxLDL as agonists. β-thromboglobulin (β-TG) levels released from platelets were also measured after incubation with or without oxLDL. Results Platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The endothelial expression of ICAM-1 is increased in atherosclerotic cell cultures and in animal models of atherosclerosis. However, in vitro studies showed that ox-LDL may either activate or inhibit platelet function such as aggregation and β-thromboglobulin secretion [ 44 ], depending on the oxidized domain and the degree of oxidation [ 45 ]. These contradictions about platelet function inhibition and activation appear to stem from the heterogeneous nature of ox-LDL.…”
Section: Platelets As a Target Of Oxidized Ldlmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelial expression of ICAM-1 is increased in atherosclerotic cell cultures and in animal models of atherosclerosis. However, in vitro studies showed that ox-LDL may either activate or inhibit platelet function such as aggregation and β-thromboglobulin secretion [ 44 ], depending on the oxidized domain and the degree of oxidation [ 45 ]. These contradictions about platelet function inhibition and activation appear to stem from the heterogeneous nature of ox-LDL.…”
Section: Platelets As a Target Of Oxidized Ldlmentioning
confidence: 99%
“…Both activated platelets and ox-LDL exert proinflammatory and procoagulant effects on several vascular cells (e.g., neutrophils, monocytes/macrophages, smooth muscle cells, endothelial cells, and platelets), thus supporting that atherosclerosis is a chronic inflammatory disease [ 44 , 49 ].…”
Section: Role Of Activates Platelets and Ox-ldl In Atherosclerosismentioning
confidence: 99%
“…oxLDL plays a central role in the initiation and progression of atherosclerosis, as it mediates the promotion of several vascular cells (e.g., neutrophils, monocytes/macrophages, smooth muscle cells, endothelial cells, and platelets). Inflammatory and pro-regulatory effects ( 14 ). The primary mechanism of macrophage formation stems from disturbances in oxLDL uptake and lipid efflux.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason is the complex action of lipids on platelets in the body. For example, naturally oxidized LDL can inhibit platelet aggregation 23 25 , which could partly explain the inconsistent results between in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%